IstikhdÄm al-MaÊ¿ajim al-Lughawiyyah fÄ« TaÊ¿alum al-Lughah al-Ê¿Arabiyyah Lada á¹¬alabah JÄmiÊ¿ah JanÅ«b Sharq UnmÅ«dhajan - Farween, A.R.F.S.; Zunoomy, M.S. (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2023)
Dictionaries play major role in providing meanings and information of vocabulary in a language. language learners take benefits widely from these dictionaries in developing their language proficiency. This study focuses the extent of the use of language dictionaries and their types among students in the Department of Arabic Language at South Eastern University of Sri Lanka who learn Arabic as a foreign language and use it as the language tool for their subjects in their university studies. This study uses the descriptive method to analyze the primary data gathered from the questionnaire and the secondary data also, while the questionnaire is distributed in Tamil language among the students of first year. The study finds that the most of the students learn Arabic alongside their mother tongue, and they also use electronic dictionaries and Google translation to understand the meanings of obscure words in their learning of the Arabic language, and they prefer bilingual and trilingual dictionaries than monolingual dictionaries, and they indicate that the use of machine translation and lack of knowledge of using dictionaries and unwillingness to use them are reasons for the lack of use of language dictionaries among them.Ø¥Ù† Ø§Ù„Ù…Ø¹Ø§Ø¬Ù… ØªØ£Ø®Ø° Ø¯ÙˆØ±Ø§ ÙØ¹Ø§Ù„Ø§ ÙÙŠ ØªÙ‚Ø¯ÙŠÙ… Ù…ÙØ§Ù‡ÙŠÙ… Ø§Ù„Ù…ÙØ±Ø¯Ø§Øª ÙˆÙ…Ø¹Ù„ÙˆÙ…Ø§ØªÙ‡Ø§ ÙÙŠ Ù„ØºØ© Ù…Ø§. Ø£Ù…Ø§ Ù…ØªØ¹Ù„Ù…Ùˆ Ø§Ù„Ù„ØºØ© ÙÙ‡Ù… ÙŠØ³ØªÙÙŠØ¯ÙˆÙ† Ø¨Ù‡Ø°Ù‡ Ø§Ù„Ù…Ø¹Ø§Ø¬Ù… Ø§Ø³ØªÙØ§Ø¯Ø© ÙƒØ¨ÙŠØ±Ø© ÙÙŠ ØªÙ†Ù…ÙŠØ© ØØµÙŠÙ„ØªÙ‡Ù… Ø§Ù„Ù„ØºÙˆÙŠØ©. ÙÙ‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© ØªØ¨ØØ« Ø¹Ù† Ù…Ø¯Ù‰ Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø§Ù„Ù…Ø¹Ø§Ø¬Ù… Ø§Ù„Ù„ØºÙˆÙŠØ© ÙˆØ£Ù†ÙˆØ§Ø¹Ù‡Ø§ Ù„Ø¯Ù‰ Ø·Ù„Ø¨Ø© ÙÙŠ Ù‚Ø³Ù… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙÙŠ Ø¬Ø§Ù…Ø¹Ø© Ø¬Ù†ÙˆØ¨ Ø´Ø±Ù‚ Ø³Ø±ÙŠÙ„Ø§Ù†ÙƒØ§ Ø§Ù„Ø°ÙŠÙ† ÙŠØªØ¹Ù„Ù…ÙˆÙ† Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„ØºØ© Ø£Ø¬Ù†Ø¨ÙŠØ© ÙˆÙŠØ³ØªØ®Ø¯Ù…ÙˆÙ†Ù‡Ø§ Ø§Ù„Ù„ØºØ© Ø§Ù„ÙˆØ³ÙŠÙ„Ø© Ù„Ù…ÙˆØ§Ø¯Ù‡Ù… ÙÙŠ Ø¯Ø±Ø§Ø³Ø§ØªÙ‡Ù… Ø§Ù„Ø¬Ø§Ù…Ø¹ÙŠØ©. Ø§Ù†ØªÙ‡Ø¬Øª Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø§Ù„Ù…Ù†Ù‡Ø¬ Ø§Ù„ÙˆØµÙÙŠ Ù„ØªØÙ„ÙŠÙ„ Ø§Ù„Ù…Ø¹Ù„ÙˆÙ…Ø§Øª Ø§Ù„Ø£ÙˆÙ„ÙŠØ© Ù…Ù† Ø§Ù„Ø§Ø³ØªØ¨Ø§Ù†Ø© ÙˆØ§Ù„Ø«Ù†Ø§Ø¦ÙŠØ©ØŒ Ø£Ù…Ø§ Ø§Ù„Ø§Ø³ØªØ¨Ø§Ù†Ø© ÙÙ‡ÙŠ ØªØªÙˆØ²Ø¹ Ø¨Ø§Ù„Ù„ØºØ© Ø§Ù„ØªØ§Ù…Ù„ÙŠØ© Ø¨ÙŠÙ† Ø·Ù„Ø¨Ø© Ø§Ù„Ù…Ø±ØÙ„Ø© Ø§Ù„Ø£ÙˆÙ„Ù‰. ÙˆÙ†ØªØ§Ø¦Ø¬ Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø£Ø¸Ù‡Ø±Øª Ø£Ù† Ø¬Ø²Ø¡Ø§Ù‹ ÙƒØ¨ÙŠØ±Ø§ Ù…Ù† Ø§Ù„Ø¹ÙŠÙ†Ø© ÙŠØªØ¹Ù„Ù…ÙˆÙ† Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø¨Ø¬Ø§Ù†Ø¨ Ù„ØºØªÙ‡Ù… Ø§Ù„Ø£Ù… ÙƒÙ…Ø§ Ø£Ù†Ù‡Ù… ÙŠØ³ØªØ®Ø¯Ù…ÙˆÙ† Ø§Ù„Ù…Ø¹Ø§Ø¬Ù… Ø§Ù„Ø¥Ù„ÙƒØªØ±ÙˆÙ†ÙŠØ© ÙˆØªØ±Ø¬Ù…Ø© Ø¬ÙˆØ¬Ù„ Ù„ÙÙ‡Ù… Ù…Ø¹Ø§Ù†ÙŠ Ø§Ù„ÙƒÙ„Ù…Ø§Øª Ø§Ù„ØºØ§Ù…Ø¶Ø© ÙÙŠ ØªØ¹Ù„Ù…Ù‡Ù…Â  Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ©ØŒ ÙƒÙ…Ø§ Ø£Ù†Ù‡Ù… ÙŠÙØ¶Ù„ÙˆÙ† Ø§Ù„Ù…Ø¹Ø§Ø¬Ù… Ø«Ù†Ø§Ø¦ÙŠØ© Ø§Ù„Ù„ØºØ© ÙˆØ«Ù„Ø§Ø«ÙŠØ© Ø§Ù„Ù„ØºØ© Ø¹Ù„Ù‰ Ø§Ù„Ù…Ø¹Ø§Ø¬Ù… Ø£ØØ§Ø¯ÙŠØ© Ø§Ù„Ù„ØºØ© Ù…Ù† Ø§Ù„Ù…Ø¹Ø§Ø¬Ù… Ø§Ù„Ù„ØºÙˆÙŠØ©ØŒ ÙˆÙŠØ´ÙŠØ±ÙˆÙ† Ø¥Ù„Ù‰ Ø£Ù† Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø§Ù„ØªØ±Ø¬Ù…Ø© Ø§Ù„Ø¢Ù„ÙŠØ© ÙˆØ¹Ø¯Ù… Ø§Ù„Ù…Ø¹Ø±ÙØ© Ø¨Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø§Ù„Ù…Ø¹Ø§Ø¬Ù… ÙˆØ¹Ø¯Ù… Ø§Ù„Ø±ØºØ¨Ø© ÙÙŠ Ø§Ø³ØªØ®Ø¯Ø§Ù…Ù‡Ø§ Ø£Ø³Ø¨Ø§Ø¨ Ù„Ù‚Ù„Ø© Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø§Ù„Ù…Ø¹Ø§Ø¬Ù… Ø§Ù„Ù„ØºÙˆÙŠØ©.